2014
DOI: 10.1007/s00259-013-2632-3
|View full text |Cite
|
Sign up to set email alerts
|

Early reduction in tumour [18F]fluorothymidine (FLT) uptake in patients with non-small cell lung cancer (NSCLC) treated with radiotherapy alone

Abstract: PurposeChanges in tumour 3′-deoxy-3′-[18F]fluorothymidine (FLT) uptake during concurrent chemo-radiotherapy in patients with non-small cell lung cancer (NSCLC) have been reported, at variable time points, in two pilot positron emission tomography (PET) studies. The aim of this study was to assess whether FLT changes occur early in response to radiotherapy (RT) without concurrent chemotherapy and whether such changes exceed test-retest variability.MethodsSixteen patients with NSCLC, scheduled to have radical RT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 30 publications
2
45
1
1
Order By: Relevance
“…The remarkable reductions in tumor uptake of 18 F-FLT preceded the changes in tumor volume, suggesting the prognostic potential of 18 F-FLT PET for monitoring early response after irradiation. These findings are consistent with previous studies using x-irradiation in murine SCCVII tumors (7,22), as well as with clinical trials (23), and a recent report demonstrated the usefulness of 18 F-FLT PET/CT imaging for predicting the therapeutic outcome of carbon ion radiotherapy in head and neck mucosal malignant melanoma (25). Furthermore, after 0.5 Gy of charged particle irradiation, tumor uptake of 18 F-FLT was significantly different from that in controls whereas tumor growth was not, indicating that the 0.5-Gy dose may not be sufficient to induce an anticancer effect in vivo.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The remarkable reductions in tumor uptake of 18 F-FLT preceded the changes in tumor volume, suggesting the prognostic potential of 18 F-FLT PET for monitoring early response after irradiation. These findings are consistent with previous studies using x-irradiation in murine SCCVII tumors (7,22), as well as with clinical trials (23), and a recent report demonstrated the usefulness of 18 F-FLT PET/CT imaging for predicting the therapeutic outcome of carbon ion radiotherapy in head and neck mucosal malignant melanoma (25). Furthermore, after 0.5 Gy of charged particle irradiation, tumor uptake of 18 F-FLT was significantly different from that in controls whereas tumor growth was not, indicating that the 0.5-Gy dose may not be sufficient to induce an anticancer effect in vivo.…”
Section: Discussionsupporting
confidence: 82%
“…because tumor hypoxia is considered an important factor for resistance to radiotherapy and appears to be an independent risk factor for tumor progression (34). 18 F-FLT, which allows monitoring of cell proliferation, is a promising tracer as a marker of early response of cell proliferation to radiotherapy (7,(22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FLT PET görüntülemenin öncelikli kullanım alanı tedaviye yanıtın değerlendirilmesidir. KHDAK'sinde hem gefitinib (bir epidermal büyüme faktörü reseptör inhibitörü) tedavisi sonrasında (76) hem de radyoterapi sonrasında (77) erken dönemde tedaviye yanıtın FLT PET görüntüleme ile değerlendirilebildiği gösterilmiştir.…”
Section: Yeni Pet Radyofarmasötikleriunclassified
“…In the context of radiotherapy, 18 F-FLT PET/CT first proved its sensitivity to ionizing radiation in preclinical tumor models (104,105). After promising results from 18 F-FLT PET/CT-based assessments of radiation response in these models, an increasing number of studies have shown that decreased 18 F-FLT uptake early (as early as 5 d/ 10 Gy) in the course of radiotherapy or chemoradiotherapy is a strong indicator of long-term outcome in a large-animal preclinical model (106) and humans (107)(108)(109)(110) (Fig. 2).…”
Section: Prognostic Role Of Molecular Imaging In Radiation Therapymentioning
confidence: 99%